Financial and Technological Trends in the Operation of Electric Vehicles by Enterprises - Muravskyi, Volodymyr; Muravskyi, Vasyl (Herald of Economics, 2026)
Modern development of electromobility is characterized by profound technological and organizational transformation of the automotive industry. The expansion of electric transport creates new operating conditions for enterprises, changing approaches to management, investment, and financial planning. The article examines current trends in the development of the electric vehicle market and their impact on the transformation of financial and managerial processes of enterprises. It is substantiated that the commercial use of electric transport generates a comprehensive positive financial effect and serves as an important driver of microeconomic change. The study identifies key technological trends in the further development of electric vehicles and determines the financial outcomes of their commercial application. It is established that the degree of transformation of an enterprise’s financial and managerial processes depends on the share of electric vehicles in the fleet, ranging from minimal changes at 1–10% to full digital and autonomous transformation at 76–100%. It is demonstrated that with the growth of electric vehicle penetration, such technological trends intensify as the extension of battery service life, integration into enterprise energy systems, software-oriented usage models, autonomous control, IoT integration, development of car-sharing, and environmental neutrality. It is determined that the commercial operation of electric vehicles ensures revenue growth, cost optimization, reduced personnel and maintenance expenses, minimized tax burden, and increased investment attractiveness of enterprises. Thus, the development of electromobility drives a comprehensive transformation of enterprises’ financial and managerial processes, leading to improved resource efficiency and enhanced economic performance. The continued expansion of electric transport creates new opportunities for innovative business models and requires the adaptation of management and accounting systems. It is shown that further technological development of electric vehicles will generate new financial effects of their use, which necessitates further scientific research.